The constellation of Lacan’s subject register in Damar Shashangka’s translation of Serat Gatholoco - Harini, Yostiani Noor Asmi; Cambara, Hegar Krisna (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2022)
Gatholoco is a figure in Serat Gatholoco, a literary work suspected to be written in the early 19th century. The Gatholoco character is said to have a constellation of desires that presents subversive symptoms, positioning Serat Gatholoco as a controversial text at that time. The aim of this study is to describe the constellation of desires in Serat Gatholoco translation from Damar Shashangka, using the economics perspective of the Lacanian subject. This study used the qualitative interpretive method. The result shows Gatholoco as a sublimation of ideas that become the image-subject in the symbolic register, which is a manifestation of alienation symptoms suppressed in the discourse of the Ruler. Naming as a true-born man declared by Gatholoco is a form of active narcissistic desire, a metonymy that connects identification and desire for Gatholoco’s self-hood. The identity of the naming is the substitution of one marker with the Other. Its word is a paternal metaphor, the substitution of the Father’s name (resistance efforts) for the Mother’s desire (primordial existence). This metaphor offers substantial resistance to the Father’s Law (puritan existence). In the end, the nicknames of Gatholoco are a form of the narcissistic desire of the author.